Cell-free hemoglobin is associated with increased vascular resistance and reduced peripheral perfusion in severe malaria - Kingston, Hugh W. F. (2021)
In severe falciparum malaria, unlike sepsis, hypotension on admission is uncommon. We hypothesized that low nitric oxide bioavailability due to the presence of cell-free hemoglobin (CFH) increases vascular tone in severe malaria.